Селітебні ландшафти в структурі угідь височинної області Волині - Ничая, Олександра Олександрівна; Nychaia, Oleksandra O.; Тарасюк, Ніна Адамівна; Tarasiuk, Nina A. (Дніпропетровський національний університет імені О.Гончара, 2016)
Відображено результати оцінювання особливостей сучасного селитебного землекористування для території височини в межах Волинської області. Динаміка структури земельного фонду Волині характеризується інтенсивним збільшенням площі забудованих земель, тобто власне селитебних ландшафтів. Селитебно-забудовані ландшафти представлено в розрізі адміністративно-територіального поділу. Для характеристики забудованих земель Волинської височини опрацьовано дані по території Горохівського та Ківерцівського районів, з виділеними ключовими ділянками КД-5 та КД-6. Установлено частку забудованих земель у структурі земельних угідь, складено матриці комплексів використання селитебно-забудованих ландшафтів. На основі аналізу побудовано цифрову векторну модель. Установлено зміну площі селитебного ландшафту та його рисунка впродовж століття. З метою оцінювання сучасного стану природокористування території визначено частку земель селитебно-житлової забудови в загальній площі забудованих територій.

The article presented the assessment results of modern inhabited land utilization in the entire upland territory within Volyn region. Dynamics of the available land structure in Volyn is marked by extreme increase in built-up area that is inhabited landscape itself. Inhabited built-up landscapes are represented in the context of the administrative and territorial division. In order to characterize built-up land in upland area of Volyn region the data from the territories of Gorohiv and Kivertsi districts were processed with singled out key areas KA -5 and KA -6. The share of built-up land in the structure of land was determined, the moulds of inhabited built-up landscapes usage were composed. Basing on the space photos and topographical maps analysis the digital vectorial model of inhabited development dynamics was constructed. Area alterations in inhabited landscape and its pattern during the century were established. For the purpose of modern nature management assessment of the territory the share of inhabited built-up development in the total area of development was determined. A number of map charts, diagrams and tables was constructed according to the results of the research work. Subsequent directions of inhabited landscapes geoecological rehabilitation were confirmed in terms of regional development.
The inhabited landscapes in the land structure of Volyn region upland area
Keywords: забудовані землі; рисунок ландшафту; природокористування; селитебно-забудовані землі; селитебно-житлова забудова; цифрова векторна модель; builtup landscapes; pattern of the landscape; nature management; inhabited builtup landscapes; digital vectorial model